2016
DOI: 10.1111/andr.12200
|View full text |Cite
|
Sign up to set email alerts
|

Absence of microsatellite instability andBRAF(V600E) mutation in testicular germ cell tumors

Abstract: SUMMARYTesticular germ cell tumors (TGCT) are the most common malignant neoplasm in young men. DNA mismatch repair deficiency can lead to microsatellite instability (MSI), an important mechanism of genetic instability. A mutation of the BRAF gene has been implicated in the pathogenesis of several solid tumors and has recently become an important therapeutic target. The role of MSI and BRAF gene mutation in TGCT, particularly in refractory disease, is poorly understood and reported findings are controversial. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…In our cohort of TGCT patients, we recently reported that well‐known hallmarks of cancer, as microsatellite instability (MSI), V600E BRAF , and TERT promoter mutations, are not present (Carcano et al ., ,b). Recently, Bagrodia et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort of TGCT patients, we recently reported that well‐known hallmarks of cancer, as microsatellite instability (MSI), V600E BRAF , and TERT promoter mutations, are not present (Carcano et al ., ,b). Recently, Bagrodia et al .…”
Section: Discussionmentioning
confidence: 99%
“…While this appears paradoxical, defective mismatch repair may cause cisplatin resistance through inducing the BRAF mutation V600E and other cisplatin resistance gene mutations. Although BRAF mutation V600E in testicular GCTs (TGCTs) has been confirmed in a separate study at a very low frequency (1%), it has not been confirmed by other two studies . A lack of functional hMLH1 or MSH6 may also lead to the bypassing of the apoptotic pathway outlined above.…”
Section: Sensitivity To Therapy In Gctsmentioning
confidence: 94%
“…However, some controversy in literature persists and more studies are needed to better explore the exact mechanism of how MMR proficiency interferes with cisplatin resistance. One study on 133 chemo-naïve primary TGCTs, 16% of which developed refractory disease, reported absence of BRAF mutations and of MSI [ 81 ]; however, studies including cisplatin-treated patient samples are more likely to tackle this matter [ 34 ]. Another mechanism worth exploring in the future is the one related to activation of translesion synthesis (TLS) induced by the absence of MMR proteins, which, in turn, potentiates skipping or bypassing of DNA adducts, again avoiding apoptotic-triggering [ 82 ].…”
Section: Dissecting Cisplatin Resistance Mechanismsmentioning
confidence: 99%